Analytical prediction of buckling collapse for reinforced thermoplastic pipes based on hoop stress analysis of crushed rings. (1st September 2019) - Liu, Wencheng; Wang, Shuqing
Abstract: Reinforced thermoplastic pipes (RTPs) can experience collapse under external pressure. The maximum external pressure that RTPs can resist before buckling collapse must be considered in engineering practice. To predict the critical pressure of RTPs, a new analytical model is proposed by analyzing the hoop stress distributions of crushed rings. The model is made under the assumption that the maximum hoop stress equals the critical stress when pipes collapse. Different from the previously reported studies, focusing on axial compression, the critical stress of cylinders' buckling under crushing loads is formulated. With regard to the material anisotropy of RTPs, the equivalent stiffness method is applied to obtain the homogenized hoop elastic modulus in the proposed model. The effectiveness of the proposed model is verified by eigenvalue analyses on solid models and continuum shell models. Compared with numerical methods and Timoshenko and Gere (1961), the proposed model was found to give accurate critical pressures and hoop stress distributions. Furthermore, the optimal range for fiber's winding angle is obtained, and the effect of thickness-radius ratios on critical pressure and the disproportionate motions of singularity points are also discussed. Highlights: A new analytical model is proposed to predict the buckling collapse of RTPs. The maximum hoop stress is determined, and the critical stress of cylinders' buckling under crushing loads is derived. The proposed model predicts accurate critical pressures and hoop stress distributions. The optimal range for fiber's winding angle is obtained. The effect of thickness-radius ratio and the disproportionate motions of singularity points are discussed.